Risk Status of Type 2 Diabetes of Working and Non-Working Women Based on Their Dietary Habits - İSLAMOĞLU, AYŞE HÜMEYRA; ÇELİK, ZEHRA MARGOT (My University, 2022)
Introduction: The working status of individuals may indirectly affect their lifestyles and dietary habits. Improper dietary habits may also cause many chronic diseases, including type 2 diabetes. In this study, it was aimed to determine the type 2 diabetes risk of working and non-working women aged between 20-59 years based on their dietary habits. Material-Method: The study was carried out with a total of 203 volunteer women – 115 working and 88 nonworking. A general questionnaire and Finnish Diabetes Risk Score (FINDRISC) questionnaire were completed by the participants. Diabetes risks were determined according to the FINDRISC scores of the participants, and compared with their working status and dietary habits. Results: There was no significant difference between the FINDRISC scores of the participants and their working status (p>0.05), but there were significant differences between their working status and their eating habits (p<0.05). It was found that working women preferred meals that were easy and took a short time to prepare like ready-to-eat or heat-and-eat, while non-working women preferred meals that took longer to prepare like home-made meals (p<0.01). In addition, working women ate out more often than non-working women (p<0.01) and on meal basis; it was determined that working women mostly ate their evening meals out, while non-working women ate their lunch out (p<0.01). Conclusion: Although no direct relationship was found between working status and type 2 diabetes risk, the results may suggest that the working status of individuals can affect their eating habits.

Giriş: Bireylerin çalışma durumu onların yaşam tarzlarını ve beslenme alışkanlıklarını dolaylı olarak etkileyebilmektedir. Uygun olmayan beslenme alışkanlıkları da tip 2 diyabet başta olmak üzere birçok kronik hastalığa neden olabilmektedir. Bu çalışmada, 20-59 yaş arası çalışan ve çalışmayan kadınların beslenme alışkanlıklarına göre tip 2 diyabet riskinin belirlenmesi amaçlanmıştır. Gereç-Yöntem: Çalışma 115'i çalışan, 88'i çalışmayan toplam 203 gönüllü kadın ile gerçekleştirilmiştir. Katılımcılar tarafından genel bilgi anketi ve Finlandiya Diyabet Risk Skoru (FINDRISC) anketi doldurulmuştur. Katılımcıların FINDISC puanlarına göre diyabet riskleri belirlenmiş, çalışma durumları ve beslenme alışkanlıkları ile karşılaştırılmıştır. Bulgular: Katılımcıların FINDRISC puanları ile çalışma durumları arasında anlamlı fark bulunmazken (p>0.05), çalışma durumları ile beslenme alışkanlıkları arasında anlamlı farklılıklar saptanmıştır (p<005). Çalışan kadınların hazır ya da ısıt-ye gibi kolay ve kısa sürede hazırlanabilen yemekleri tercih ettikleri, çalışmayan kadınların ise ev yemekleri gibi hazırlanması daha uzun süren yemekleri tercih ettikleri belirlenmiştir (p<0.01). Ayrıca, çalışan kadınların çalışmayan kadınlara göre daha sık dışarıda yemek yediği (p<0.01) ve öğün bazında; çalışan kadınların en çok akşam yemeğini, çalışmayan kadınların ise öğle yemeğini dışarıda yedikleri saptanmıştır (p<0.01). Sonuç: Çalışma durumu ile tip 2 diyabet riski arasında doğrudan bir ilişki saptanmamış olsa da, sonuçlar bireylerin çalışma durumunun beslenme alışkanlıklarını etkileyebildiği düşünülmektedir.
Çalişan ve çalişmayan kadinlarin beslenme alişkanliklarina göre ti̇p 2 Di̇yabet ri̇sk durumu
Keywords: Diyabet riski; Çalışma durumu; Beslenme alışkanlıkları.; Diabetes risk; Working status; Dietary habits